PENGUATAN KOMPETENSI NUMERASI ABAD KE-21 BERBASIS ETNOMATEMATIKA MELAYU DAN NILAI ISLAM PADA SISWA SERI-SEMI ABIM MALAYSIA - Yulia Rahmawati Z; Ade Rahman; Hera Hastuti (Lembaga Penelitian dan Pengabdian Pada Masyarakat Universitas Tamansiswa Padang, 2026)
This community engagement program aimed to strengthen twenty-first-century numeracy competencies through a Malay ethnomathematics approach integrated with Islamic values for students of Sekolah Rendah Islam (SERI) and Sekolah Menengah Islam (SEMI) ABIM Malaysia. The program adopted a Participatory Learning and Action (PLA) approach through three main activities: interactive sharing sessions, educational counseling, and simple hands-on practices based on Malay cultural heritage. Learning materials utilized Malay songket motifs, the congkak traditional game, Malay traditional houses, and wau as contextual media for numeracy learning while integrating Islamic values, including mizan (balance), itqan (excellence), amanah (responsibility), and ta'awun (cooperation). The implementation showed active student participation through discussions, cultural exploration, and group presentations. The program provided meaningful learning experiences, enhanced students' appreciation of Malay cultural heritage, and strengthened their understanding that mathematical concepts can be learned through cultural contexts and Islamic values. This program offers an alternative contextual and culturally responsive model for strengthening numeracy learning in Islamic schools.